Hubungan Tingkat Pengetahuan dan Perilaku Swamedikasi Magh pada Mahasiswa di Universitas Abdurrab - Sisri Novrita; Fredi; Sri Kartini; Adrian Mulya (JURNAL FARMASI DAN MAKANAN, 2025)
Magh or gastritis is a disease that arises due to inflammation of the gastric mucosa which can cause symptoms such as heartburn, flatulence, nausea, vomiting, and other digestive disorders. Magh often occurs among students who have high levels of stress and habits that tend to be irregular. Magh is a common disease that can be treated with self-medication or self-treatment with medications without a doctor's prescription. The level of knowledge and behavior in self-medication plays an important role in the success of treatment to obtain maximum therapeutic results. This study aims to determine the relationship between the level of knowledge and self-medication behavior in students at Abdurrab University. The research design used was observational analytics with a cross sectional research design. The sample collection technique used stratified random sampling with a sample of 315 respondents who met the inclusion criteria. The results of the study showed that the level of knowledge of students had good knowledge, namely 201 respondents (63.8%). The self-medication behavior of magh students had sufficient behavior, namely 129 respondents (49.5%). Based on the results of the Chi Square correlation test, it can be concluded that there is no relationship between the level of knowledge and self-medication behavior in students at Abdurrab University Pekanbaru with a p value of 0.102 (>0.05). Keywords: Knowledge, Behavior, Self-Medicine, Magh, Students